Ka haere tonu te mana o ngā wahine Māori : Māori women as protectors of te ao Māori knowledge : a thesis presented in partial fulfilment of the requirements for the degree of Master in Social Work at Massey University, Palmerston North, New Zealand - Ruwhiu, Paulé Aroha (Massey University, 2009)
Māori women play a critical role in whānau, hapū and iwi as whare tangata (procreators) and as whare mātauranga (repositories of knowledge). Wahine hold specific knowledge pertaining to their roles and responsibilities. As the primary nurturer to their young, they have a prime opportunity to provide this essential knowledge to the next generation. Historically, this occurred through oriori; however in recent times these processes have evolved to include technological advancements in communication. This research examined the nature of te ao Māori knowledge and the processes used to transmit it through three generations of Māori women in three whānau. It explores the roles and responsibilities of Māori women in pre-colonial Māori society, the influences of the colonisation process and Māori women’s resilience to continue to pass on the practices of their tūpuna. The methodology drew on aspects of three different theories in order to address the needs of the participants as historically oppressed, minority indigenous Māori women. Critical theory acknowledged the oppression and minority status as well as encouraging the sharing of experiences. Kaupapa Māori theory localised the issues of Māori in relation to the colonisation process and mana wahine theory identifies the significant roles and responsibilities of Māori women as leaders/agents of change within their whānau, hapū and iwi. A qualitative approach allowed the information gathered to be conducted similarly to Māori oral traditions. It was identified from the understandings gathered from the participants that significant te ao Māori knowledge has been passed down through the generations. It also showed that the knowledge has changed from generation to generation and the passing on of knowledge has also changed due to the social and technological advancements associated with development and outside influences on the younger generation. This thesis confirms that Māori women are resilient and some have been able to continue to pass on te ao Māori knowledge despite the challenges of the rural to urban shift and the effects of colonisation. It also encourages women and whānau who have not been privilege to this knowledge to begin the journey to reclaim their right and provides some strategies for doing this. It celebrates the voices of three whānau who have demonstrated their strength to maintain the philosophies of traditional Māori.
Keywords: Maori women; Wahine Maori; Maori knowledge; Fields of Research::420000 Language and Culture::420300 Cultural Studies::420306 Maori cultural studies